Strengthening enterprise competitiveness by synchronizing supply chain - Jasinavičius, Rimvydas; Jasinavičius, Nerius (Business: Theory and Practice, 2011)
When competition is fierce and many producers try to create a competitive advantage by lowering prices, price wars are very common, but only few survive. Low prices erode producers’ margins and economic viability of the company. Low prices are very short- lived competitive advantage as it can be easily imitated by other competitors. Only producers with big economies of scale and low labour costs can afford very low sales prices. Eastern European producers have neither economies of scale nor low labour costs (comparing to Far East producers). This paper provides theoretical background and practical experience of how three Eastern European textile producers created significant competitive edge, which enabled them to increase their customer base more than three times. Profitability has increased by 4 times, and net-profit by 5 times.